ACD e questão agrária : práticas discursivas jurídicas nas disputas fundiárias em Mato Grosso - Brandão, Álvaro José Antunes (2023)
The research in question analyzes a judicial process, specifically, a criminal action that involves a massacre of indigenous people from the Cintas Largas, in the Paralelo 11 region, in the north of the state of Mato Grosso. This is the dialogue with the typical scientific/historical processes on the frontier of the expansion of capitalism, in no case, mainly due to the extraction of poaia, latex and minerals. The legal process that reports the event brings to light a series of social/discursive practices, which are ideologically located between power relations. Therefore, if power dynamics are expressed textually, it is possible to locate patterns or discursive inflections, which demonstrate a modus operandi guided by relations of interests, especially economic and colonial interests. To analyze this context, theoretical/methodological tools from Critical Discourse Analysis (FAIRCLOUGH, 2003) will be used, supported by SystemicFunctional Linguistics (HALLIDAY, 1985; 1994) and decolonial studies (QUIJANO, 2005 ; CÉSAIRE, 2020; FANON, 2005; OLIVEIRA; FREIRE, 2006). From ACD, it is possible to analyze the relationships of texts using the Intertextuality category, through the actional meaning of the discourse, perceiving the chain of genres generated by the legal system, both between the regulations (Federal Constitution, Penal Code and Code of Procedure Penal), as well as the theoretical support that supports them, such as Penal Guarantee (FERRAJOLI, 2002). Through this proposal, it is possible to understand the way in which legal institutions are (dis)accommodated based on the procedural relationships established in the records.